LEVEL OF PHYSICAL ACTIVITY AND BODY COMPOSITION IN ADOLESCENTS (Fiep Bulletin - online, 2019)
It is known that regularly practiced physical activity can bring several benefits among them: weight maintenance, boneand functional strengthening, blood pressure reduction and control and diabetes. The objective of this study was to analyze thelevel of physical activity and body composition of adolescents working in the rotary parking lot in the city of Itapeva, SP. After theinvitation, 14 young women with a mean age of 18.9 ± 0.92 years accepted to participate in the study. They were submitted toanthropometric assessments and physical activity level. The body composition was evaluated by BMI, it was calculated dividingbody mass in kilograms by height in square meter squared. The BMI classification was performed by four strata: underweight,adequate weight, overweight and obesity, and the level of physical activity by the IPAQ questionnaire (short version). The resultsindicate that 72% present within normal, 21% with excess weight. The level of physical activity indicated that 71% are physicallyactive, 29% are very physically active, there was no presence of physical inactivity. It is suggested that the volunteers studiedshowed levels of body composition within normality and level of regular physical activity. Strategies that encourage adolescentsto practice regular physical activity contribute to maintenance of fat percentage and physical activity level at normal levels.